Türkiye’de Sanatçı Adayı Yetiştiren Yükseköğretim Kurumlarının 2000 Yılı Sonrası Gelişimi / Development of Turkish Higher Education Institutions Educating Candidate Artists After 2000 - Çağlayan, Evrim; Kıratlı, Ayşe Dilek (Journal of History Culture and Art Research, 2017)
Abstract The aim of this study is to present the qualitative development of Turkish higher education institutions that educating candidate artists after 2000. Obtained data and documents were organized according to this development and were analyzed in order to provide current information about these higher education institutions. The study deals with two main themes. The first theme contains developments between 1983 and 2000, and the second theme contains developments between 2000 and 2016. In the study, it has been found that the number of higher education institutions that training candidate artists follow a steady increase after 2000 and their numbers reached to 70 in 2016. The relevant literature show that some faculties of fine arts were established without planning and analysis about the needs of academic and administrative staff, technical and spatial structure, employment opportunities after graduation. Because of this reason, these faculties could not reach a sufficient number of academic staff, could not provide the minimum physical conditions and could start education approximately 3 or 4 years after their establishment. Öz Bu çalışma, sanatçı adayı yetiştiren yükseköğretim kurumlarının 2000 yılı sonrası niceliksel gelişimini ortaya koymayı amaçlamaktatır. Çalışma ile ilgili elde edilen bilgi ve belgeler bu gelişim sürecine göre düzenlenmiş ve ilgili yükseköğretim kurumları hakkında güncel bilgileri sunmak amacıyla analiz edilmiştir. Çalışma bulguları iki ana tema üzerinden sunulmuştur. Birinci tema 1983-2000 yılları arasında yaşanan gelişmeleri, ikinci tema ise 2000 yılından günümüze kadar olan gelişmeleri kapsamaktadır. Çalışmada, sanatçı adayı yetiştiren yükseköğretim kurumlarının sayısının 2000 yılı sonrasında düzenli bir artış izlediği ve 2016 yılında 70’e yükseldiği tespit edilmiştir. Çalışma sonucunda; yeterli planlama, mezuniyet sonrası istihdam olanakları, teknik ve mekânsal altyapı ihtiyaçları, akademik ve idari kadrolar, aday öğrenci kaynakları gibi hususlar göz ardı edilerek yeni fakültelerin kurulduğu tespit edilmiştir. Bu nedenle, pek çok fakültenin yeterli öğretim elemanı sayısına ulaşamadığı, asgari fiziki koşulları sağlayamadığı ve kuruluşlarından ancak 3-4 yıl sonra eğitim-öğretime başlayabildikleri belirlenmiştir.